Evaluasi Sistem Informasi Monitoring dan Evaluasi Pembangunan (Simonep) dengan Pendekatan It Balanced Scorecard (Studi Kasus : Kantor Bappeda Kabupaten Karimun) - Idria Maita; Rudi Fithriansyah (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2015)
Karimun Regency is one of regencies in Riau Islands menggunkana Monitoring and EvaluationInformation System Development (SIMONEP). SIMONEP is used for monitoring and evaluation ofdevelopment activities originating from budget funds and state budget. Since 2010, the implementation ofthis SIMONEP has not been evaluated. To determine whether the system is still in accordance with theobjectives of the organization, the purpose of this study was to evaluate SIMONEP in aligning the vision,mission and objectives of the organization of the Information Technology (IT) is SIMONEP. The methodused is the IT Balanced Scorecard. This method is a measurement method that is developed to formulatea strategic plan to equalize the vision of the organization and the vision of the IT Division, the mission ofthe organization and the mission of the Division of IT, the company's strategic objectives with IT Divisiongoals. The success rate of implementation BAPPEDA's SIMONEP on Karimun measured by evaluatingSIMONEP using IT Balanced Scorecard. Measurements by determining the percentage of successfulimplementation of strategic objectives by using the technique of adjustment and measured usingtechniques averages then describe the results of an evaluation using a kite diagram. This evaluationresulted in the development advice on the implementation of Monitoring and Evaluation InformationSystem Development (SIMONEP) to improve the quality of implementation in order to achieve specifictargets.Keywords: Adjustment, Average, Evaluation, IT Balanced Scorecard ,SIMONEP.